The Effect of Gracilaria verrucosa Extract Feeding to the Blood Glucose Content of White Rats (Rattus norvegicus) - S.A., Candra Tama; Dewi, Eko Nurcahya; Ibrahim, Ratna (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2012)
Food fibre could retard the absorption of glucose into blood. Gracilaria verrucosa seaweed  species contains high food fibre. The objective of the study was to investigate the effect of different doses of G. verrucosa extract fed on white rats (Rattus norvegicus) to the blood glucose after one and two hours feeding of extract. The results  indicated  that  the  different  G.  verrucosa  extract  doses  fed  on  white  rats  caused  highly  significant difference in the blood glucose contents from the blood samples of the treatments after one hour and two hours feeding time. The blood glucose contents were highly significant lower compared to the control. The highest dose was 4.5 g/kg body weight could reduce 53.65% of blood glucose content. Keywords : Gracilaria verrucosa, white rats, blood glucose.